LAHIA: an integrated approach to addressing livelihoods, agriculture and health - Avakyan, Yeva (2018)
Yeva Avakyan POLICY SEMINAR Addressing gender and social barriers to resilience: Measuring and leveraging household decision making for resilience Co-Organized by IFPRI and Mercy Corps JUN 27, 2018 - 09:30 AM TO 11:00 AM EDT